Disparities in entrepreneurship indicators across EU countries - Angulo-Guerrero, María José; Pérez-Moreno, Salvador Jesús; Abad-Guerrero, Isabel María (My University, 2015)
The levels and characteristics of entrepreneurship differ widely across EU member countries due to diverse cultural, educational, economic-financial and institutional reasons. Taking as reference data provided by the Global Entrepreneurship Monitor (GEM), this paper analyzes the disparities in entrepreneurship indicators among the EU member countries in 2007 and 2013, highlighting the most significant changes occurred during the Great Recession. For this purpose, some of the major indices of inequality have been calculated, namely the Gini, Theil and Atkinson indices. In addition, the change in the Gini coefficient between these two years is additively decomposed into mobility and progressivity components, and growth incidence curves of some key indicators of entrepreneurial activity are estimated. Overall, we find that inequality among countries in most entrepreneurial attitude and aspiration indicators tends to diminish over the period 2007-2013. For all indicators the reduction is more generalized across the efficiency-driven economies than across the innovation-driven economies.
Keywords: Empresas - Gestión; Entrepreneurship; GEM indicators; Inequality